Analisis Iklim Mikro Kawasan Berdasarkan Kerapatan Bangunan dan Vegetasi di Kawasan Institut Teknologi Bandung (ITB) Kampus Ganesha Bagian Selatan - Annisa Binti Nolasari; Wardatut Toyyibah; Kurniawan, Abhi; Dyah Rembulan W.S; M. Fadhlul Wafi Chandra; M. Donny Koerniawan (LPPM Universitas Terbuka, 2023)
This study was conducted with the goal to identify parameters for a comfortable and cool outdoor environment, particularly in a tropical country like Indonesia. However, no previous research has been conducted to investigate the relationship between building configuration, vegetation density, and climatic conditions in campus areas, particularly the ITB Ganesha campus. As a result, the purpose of this research is to identify and analyze the microclimate on the ITB Ganesha campus using Envi-MET simulations. Thermal comfort factors affected by building configuration and vegetation density are examined in order to determine the relationship between those factors and microclimatic conditions in the campus area. This study employs quantitative methods, including simulation using ENVI-met software and comparison of the characteristics of the areas with data from the simulation. According to the findings, areas with higher vegetation density and lower yet more organized building configurations are cooler and more comfortable than areas with lower vegetation density and lower yet less organized building configurations. This research could lead to new insights for campus planning and development, as well as help create a healthy and comfortable environment on the ITB Ganesha campus while facing the global climate crisis. Aside from that, this study can be used as a reference for decision-making in the field of urban and environmental planning to improve life quality by improving outdoor environmental quality.